1998
DOI: 10.5014/ajot.52.7.531
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Measure of Adolescent Leisure Interests

Abstract: The ALIP appears to have good reliability and may be useful as a clinical and research tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 10 publications
1
48
1
Order By: Relevance
“…In a review of the literature, we found only six empirical studies comparing dimensions of activity participation for children with and without physical disabilities (Brown & Gordon, 1987;Henry, 1998;Margalit, 1981;Sillanpaa, 1987;Stevens et al, 1996;Stevenson, Pharoah, & Stevenson, 1997). These studies indicated that children with disabilities engaged in less varied leisure activities, more quiet activities, and fewer social activities, especially those of a spontaneous nature (Brown & Gordon, 1987;Margalit, 1981;Sillanpaa, 1987).…”
Section: The Activity Participation Of Children With Physical Disabilmentioning
confidence: 91%
“…In a review of the literature, we found only six empirical studies comparing dimensions of activity participation for children with and without physical disabilities (Brown & Gordon, 1987;Henry, 1998;Margalit, 1981;Sillanpaa, 1987;Stevens et al, 1996;Stevenson, Pharoah, & Stevenson, 1997). These studies indicated that children with disabilities engaged in less varied leisure activities, more quiet activities, and fewer social activities, especially those of a spontaneous nature (Brown & Gordon, 1987;Margalit, 1981;Sillanpaa, 1987).…”
Section: The Activity Participation Of Children With Physical Disabilmentioning
confidence: 91%
“…Only a few studies have compared the participation of children, youth, or young adults with and without physical disabilities outside school time (Anderson & Clarke, 1982;Brown & Gordon, 1987;Henry, 1998;Margalit, 1981;Sillanpaa, 1987;Stevens et al, 1996;Stevenson, Pharoah, & Stevenson, 1997). These studies generally have small sample sizes (less than 100 participants) and, for the most part, focus either on social or leisure activities outside the home (e.g., Sillanpaa, 1987;Stevens et al, 1996;Stevenson et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…It is important not to assume that more participation is better (Henry, 1998;King et al, 2003); rather, what is important is the fit with the child's wants and desires, as there clearly are individual differences in what children want to do. The present study does not address the meaning of participation experiences, other than examining enjoyment of activities.…”
Section: Introductionmentioning
confidence: 98%
“…Sloper et al (1990) found that only 56% of children with Down syndrome participate in formal, organized activities. However, a recent study indicated that children and youths with disabilities are participating actively and in the same types of activities as children and youths without disabilities (Henry 1998). There have been no recent large studies focusing specifically on the nature of the participation of children and youths with physical disabilities.…”
mentioning
confidence: 99%